Правосуддя як мета та мета правосуддя (до питання про філософію правосуддя) - Бігун, B.C. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье рассматриваются вопросы философии правосудия. Автор разграничивает понятия правосудие как цель и цель правосудия, основыываясь на разграничении понятий правосудие и судопроизводство. Дается критический анализ определения правосудия как цели в понимании его соответствия требованиям справедливости и эффективного возобновления в правах. The article examines issues of the philosophy of justice as judicial process. Differentiating concepts of justice as purpose and purpose of justice based on differentiating concepts of justice and legal proceeding, the author points out that the first concept corresponds to the idea that justice as judicial process should adhere to the requirements of justice and provide effective renewal of rights whereas the second concept of justice aims at providing fair judicial process. The author differentiates the essence and the form of justice, examining it as just trial which must correspond to the requirements of justice and constitute justice.